The burden of musculoskeletal diseases in the general population of Spain: results from a national survey - Carmona, L; Ballina, J; Gabriel, R; Laffon, A (Annals of the rheumatic diseases, 2001)
OBJECTIVE The objective of the EPISER study was to estimate the prevalence of rheumatoid arthritis (RA), low back pain, hand and knee osteoarthritis (OA), and fibromyalgia in the adult Spanish population, and to assess the impact of these diseases on function and quality of life, and use of health and social resources. METHODS 2998 subjects aged 20 years or above were randomly selected by stratified multistage cluster sampling from the censuses of 20 municipalities. Trained rheumatologists carried out structured visits at which subjects were asked about rheumatic symptoms and sociodemographic characteristics, completed validated instruments for measuring function (HAQ) and quality of life (SF-12), and underwent a standardised physical examination. Cases were defined by previously validated criteria. RESULTS The estimated prevalences with 95% confidence intervals were as follows: RA lifetime cumulative: 0.5% (0.3 to 0.9); low back pain: 14.8% (12.2 to 17.4); symptomatic knee OA: 10.2% (8.5 to 11.9); hand OA: 6.2% (5.9 to 6.5); fibromyalgia: 2.4% (1.5 to 3.2). Most conditions significantly impaired function and quality of life. CONCLUSIONS The EPISER study has internal and external validity for application of the results to the adult Spanish population. The diseases studied affect a significant proportion of the population, with various degrees of impact on disability and quality of life resulting in a significant number of physician visits, work disability, and medication use.